The Connotation, Features, and Mechanism of Computational Propaganda - Yang, Jin (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The purpose of the work is to identify the connotation, features of computational propaganda and reveal how computational propaganda uses new technologies to manipulate public opinion. The study’s hypothesis is the assumption that computational propaganda, as a new type of propaganda and manipulation of public opinion spawned in the era of artificial intelligence, stealthily and massively steers public opinion using new technologies to influence political and social processes. With the scientific methods such as event analysis and case-study, the work concludes that more and more governments, political parties, and strategic communication companies use social media as the digital platform, Internet bots as the automated executors, and algorithms as the computational technical guarantee, by participating in, guiding and creating controversial topics and events, to manipulate public opinion and win international competitions, policy debates, elections, etc.

Celem pracy jest zidentyfikowanie konotacji, cech propagandy obliczeniowej oraz ujawnienie, w jaki sposób propaganda obliczeniowa wykorzystuje nowe technologie do manipulowania opinią publiczną. Hipotezą badania jest założenie, że propaganda obliczeniowa, jako nowy rodzaj propagandy i manipulacji opinią publiczną, zrodzony w erze sztucznej inteligencji, potajemnie i masowo steruje opinią publiczną za pomocą nowych technologii, aby wpływać na procesy polityczne i społeczne.
Konotacje, cechy i mechanizm propagandy obliczeniowej
Keywords: computational propaganda; manipulation; social media; Internet bots; algorithms; propaganda obliczeniowa; manipulacja; media społecznościowe; boty internetowe; algorytmy